The Influence of Work-Life Balance and Work Motivation on the Job Satisfaction of Harvest Employees at PT Rezeki Kencana Estate Deras - Husni Mubarok; Eru Ahmadia (SAINTIS Publishing, 2026)
This study analyzes the influence of work-life balance and work motivation on the job satisfaction of harvest employees at PT Rezeki Kencana Estate Deras. The research aims to understand how the alignment between work responsibilities and personal life, along with motivational conditions, shapes employee satisfaction in a labor-intensive plantation environment. A quantitative associative design was used, involving the entire population of permanent daily workers assigned to harvesting activities, totaling 109 respondents. Primary data were collected through interviews with the personnel department and structured questionnaires, while secondary data were obtained from company reports on production, attendance, and employee composition. All measurement items met the required standards of validity and reliability, and the dataset fulfilled the assumptions for regression analysis. The results indicate that work-life balance and work motivation each have a positive and significant effect on job satisfaction, and both variables collectively explain 30% of its variation. These findings highlight the importance of workplace policies that support a healthy balance between work and personal life, as well as motivational practices that maintain employee engagement and well-being. The study contributes to the literature by providing empirical evidence from the plantation sector, a context that remains underrepresented in job satisfaction research. Future studies are encouraged to include additional organizational and individual factors or employ longitudinal approaches to capture changes in employee attitudes over time.